O que os olhos não veem, o coração sente: dramáticas do tradutor técnico - Campos, Marcella Machado de (2014)
The objective of this master´ s dissertation is to make comments on the technical translator´ s present working conditions in Brazil by considering the translation activity as a labour dramaturgy in which the professional is continuously required to make choices and to weigh up his management decisions according to distinct and sometimes contradictory values. Therefore we use the theoreticmethodological principles of Ergology and the notions of producing conditions, primacy of the inter-discourse and inter-incomprehension, which is regulated in the framework of the French Discourse Analysis. The justification of the present research resides in the fact that there is a dearth of studies which deal with the translator´ s daily life and raise socio-historical questions that are implied in the activity of technical translation. Taking into consideration the ergologic premise, which is to closely observe what occurs in the actual activity, it was necessary to re-normalise the approximation of the situation of the technical translator´ s work in virtue of the difficulties which appeared with respect to the methodology. Thus, in order to approach the object of the study, the research proposal was made viable by means of a questionnaire, which was administered to voluntary translators, as a way of suggesting a reflection about what this professional does and how he/she does it with the purpose to provide a greater self-awareness as a worker. Thus our primary research interest focuses on the way in which the translator performs his/her task, that enables him/her to perceive his/her condition in the present time from a different perspective, which, in the ultimate analysis, can occasion an improvement of the quality of the services he/she renders